2017
DOI: 10.1159/000455947
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Tricuspid Regurgitation in the First Trimester as a Screening Marker for Congenital Heart Defects: Systematic Review and Meta-Analysis

Abstract: Background: Assessment of tricuspid flow has been reported to improve the performance of screening for aneuploidies and congenital heart defects (CHD). However, the performance of tricuspid regurgitation (TR) as a screening marker for CHD in euploid fetuses is yet to be established. The main aim of this meta-analysis was to establish the predictive accuracy of TR for CHD. Methods: MEDLINE, Embase, and the Cochrane Library were searched electronically utilizing combinations of the relevant medical subject headi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Study objectives, eligibility criteria, outcome definitions, search strategy, process of data extraction, statistical analyses, and method of study quality assessment were all defined in a protocol. Investigators are experienced in systematic reviews [20][21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…Study objectives, eligibility criteria, outcome definitions, search strategy, process of data extraction, statistical analyses, and method of study quality assessment were all defined in a protocol. Investigators are experienced in systematic reviews [20][21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…Durante el primer trimestre del embarazo, los estudios sobre detección del SdD han demostrado que la evaluación de la TN fetal combinada con las pruebas bioquímicas, con tasa de falsos positivos de 5 %, tiene un porcentaje de detección de 78,7 % (intervalo de confianza del 95 %, 66,3 % -88,1 %) (9). Un estudio Entre las 11-14 semanas de gestación, la regurgitación tricúspidea ocurre aproximadamente en 5 % de los fetos normales, mientras que 70 % de los fetos con SdD presentan esta alteración (34,35). Existe evidencia que demuestra que, durante el primer trimestre del embarazo, cuando se incluyó la regurgitación de la válvula tricúspidea en la evaluación ecográfica, la tasa de detección del SdD fue superior al 90 % (36).…”
Section: Aumento De La Translucencia Nucal Fetal Y Aneuploidías Fetalesunclassified
“…Tricuspid regurgitation is observed in 1% of euploid fetuses compared to over half of fetuses with trisomy 21 and about a third of fetuses with trisomy 18, 13, or Turner syndrome [32]. A recent review reported that first trimester tricuspid regurgitation was associated with a 10-fold increase in congenital heart disease [33].…”
Section: Us Echocardiography Fetalmentioning
confidence: 99%